Pelatihan Memahami Tenses Siswa Kursus Bintang Mulia Sei Balai Kabupaten Batubara - Sri Rezki Maulina Azmi; Akmal Akmal; Muthia Dewi (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2021)
Abstract:This training is one of facilitaties to the students to understand about the english tenses of structure very quickly and accurately. This devotion to the community (society) was done to the students who were studying at the Training Course Bintang Mulia Kecamatan Sei Balai Kabupaten Batu Bara. This study used the qualitative research by explaining very shortly and by doing the exercises or simulation. In this training, the students were also given a chance or a few chances in asnwering the questions in the exercises when the training were doing. The amount of participants were 20 (twenty) persons or students who were actively studying either in the computer or English. Keywords: Tenses, Training, Devotion to society.  Abstrak: Pelatihan ini merupakan sarana bagi para peserta didik atau siswa untuk memahami tenses Bahasa Inggris dengan mudah dan akurat. Pengabdian kepada masyarakat ini diperuntuk bagi siswa yang sedang belajar di LKP Bintang Mulia Sei Balai Kabupaten Batu Bara. Metode yang dipergunakan adalah dengan cara kualitatif dengan memberikan penjelasan singkat dan dengan melakukan simulasi atau latihan. Dalam pelatihan, para siswa juga diberi kesempatan untuk menjawab pertanyaan dalam bentuk latihan ketika proses pelatihan sedang berlangsung. Jumlah peserta adalah 20 siswa yang sedang aktif belajar baik belajar komputer ataupun Bahasa Inggris. Kata Kunci: Tenses, Pelatihan, Pengabdian masyarakat.